The Relationship Between Alexithymia and Smartphone Addiction Among Adolescents in Surabaya - Fathiya Luthfil; Yuanita Wulandari; Gita Marini; Yesicha Novia Edwin Darini; Mariyatul Kiptiyah (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2026)
Alexithymia is characterized by difficulties in identifying and expressing emotions and is considered to play an important role in influencing excessive gadget use among adolescents. This study aimed to determine the relationship between alexithymia and gadget addiction among adolescents using questionnaires to assess the level of alexithymia and smartphone addiction. This study employed a descriptive correlational design with a cross-sectional approach. The population consisted of 188 adolescents, with 130 respondents selected through non-probability purposive sampling. The independent variable was alexithymia, while the dependent variable was gadget addiction. Data were collected using the Alexithymia Questionnaire and Smartphone Addiction Questionnaire and analyzed using the Pearson correlation test with a significance level of α = 0.05. The results showed that most respondents experienced smartphone addiction at a high level. Statistical analysis revealed a significant relationship between alexithymia and gadget addiction, with a p-value of 0.000 (p < 0.05) and a correlation coefficient of 0.451, indicating a moderate positive correlation. Therefore, adolescents with higher levels of alexithymia tended to experience higher levels of gadget addiction. These findings suggest the importance of emotional regulation and psychological interventions in preventing gadget addiction among adolescents